Lactic Acid Bacteria from Indigenous Fermented Foods and Their Antimicrobial Activity - Endang S. Rahayu; Titiek F. Djaafar; Djoko Wibowo; Slamet Sudarmadji (Indonesian Food and Nutrition Progress, 1996)
Twenty-eight lactic acid bacteria ( LAB) strains were isolated from various indigenous fermented foods, i.e., asinan rebung (bamboo shoot pickle), asinan terong (eggplant pickle), gatot(fennented dried cassava), growol (fermented raw cassava), tape (fermented steamed cassava tubers), tempe (fermented soybean), tempoyak (fermented pulp of durian fruit), andmoromi. All strains found and identified belong to facultative heteroÂ¬fermentative group lactobacilli. They produced DL-lactic acid, and contained meso-diaminopimelic acid in their peptidoglycan, and were identified as Lactobacillus plantarum and L pentosus complex. These strains were further determined for their antimicrobial activity against Staphylococcus aureus using disc assay and turbidimetric assay. Two among them, Lactobacillus TGR-2 (from growol) and Lactobacillus TMO-4 (from moromi) were able to increase the lag phase, and to suppress the final population of the S. aureus growth after 12 h incubation.